Answers

The Brainliest Answer!
2014-06-20T11:05:52+05:30
It is given that 3 -√2/(3 + √2)=a+b 
solving 
3-√2/3+√2=3-√2/3+√2 *3-√2/3-√2   in this step we have rationalised by 3-√2
this will give you (3-√2)²/9-2   using (a+b)(a-b)=a²-b²
=9+2-6√2/7
=11=6√2/7
=a=11/7 
b=6/7    by comparing a+b√2 by our ans

sorry it was my mistake it is -6/7 as while comparing a+b√2=11+(-6√2)/7 
once again sorry! so b=-6/7

2 5 2
but the value of b is given -6/7
in case of a doubt reply back
ya in the answer sheet given to us the value of b is -6/7 not 6/7
is it ok now!
ya thanks